Tensile stress-strain models for high strength steels. (November 2021) - Wang, Xing-Qiang; Tao, Zhong; Katwal, Utsab; Hou, Chao
Abstract: In recent years, high strength steels (HSSs) with a minimum nominal yield stress of 460 MPa have been increasingly used in structural applications. An HSS may exhibit continuous or discontinuous yielding, depending on the chemical composition and manufacturing process and procedure. However, no criterion has been proposed in the literature to predict the occurrence of a yield plateau. Meanwhile, the ductility of HSSs is often limited, making it essential to predict their fracture for a safe design. However, existing stress-strain models used for HSSs cannot meet this need. To develop versatile stress-strain models for HSSs, 212 test curves are collected from open literature. In addition, four curves are obtained from tensile tests of two types of HSS produced in Australia (Bisalloy 80 and 400). By analysing the collected test data, a criterion is proposed to determine the occurrence of the yield plateau according to the yield stress of the steel and its carbon content. Two stress-strain models are then proposed for HSSs exhibiting continuous and discontinuous yielding, respectively. Moreover, predictions from the discontinuous model are also compared with the test data of conventional mild steel, proving that the model can also capture the stress-strain response of the conventional mild steel. Finally, the proposed models are used in the simulation of HSS coupons and beams, which proves the feasibility of the proposed HSS models for structural analysis. Graphical abstract: Unlabelled Image Highlights: A criteria is proposed to predict the yield plateau occurrence of HSS. Two stress-strain models are proposed for HSSs with or without a yield plateau. The discontinuous yielding model can also be used for conventional mild steel. The proposed models have been used in the simulation of HSS coupons and beams.